Perioperative ultrasound among South African anaesthetists: a survey of current practice and availability - Kathrada, Mohammad (Department of Anaesthesia and Perioperative Medicine, 2024)
Background: Point-of-care ultrasound (POCUS) is becoming part of the standard skill set of the modern-day anaesthetist. There is limited knowledge regarding the availability of ultrasound (US) and POCUS skills in South Africa. There may be barriers to adopting US in many institutions. Methods: An observational cohort questionnaire was distributed via an online REDCap survey. All doctors practising anaesthesia in South Africa were eligible. Recruitment was done via an email link that was sent to South African Society of Anaesthesiologists (SASA) members. Non-SASA members were recruited via departmental mailing lists or social media. Results: Of the 580 respondents, 478 were SASA members (response rate 22.9%, confidence interval 3.94) and 102 were non-SASA members. In total, 571 surveys were suitable for analysis, 397 (69.5%) respondents had more than five years anaesthesia experience, 558 (97.7%) of respondents worked in hospitals that have US machines available, and 76.7% had US readily available after hours. Respondents used US mostly for central venous catheter (CVC) insertions (77.9%), regional anaesthesia (82.3%), and cardiac and lung assessments (26.4% and 17.7%, respectively). It is used much less frequently for neuraxial anaesthesia (1.4%). Of the respondents, 382 (66.9%) had received US training, only 198 (34.7%) felt confident in their US skills, and 482 (84.4%) wish to have further US training. The two most significant barriers to US were lack of equipment and lack of training at postgraduate level. Conclusion: South African anaesthetists work at institutions where US equipment is generally available, and most practitioners want to incorporate US in their practice. However, anaesthetists feel insecure with respect to their skills and indicated that they wish to receive further training. Efforts should be made to formalise POCUS training in the Fellowship of the College of Anaesthetists (FCA) curriculum and make US training more accessible.